Capping the calix: how toluene completes cesium(i) coordination with calix[4]pyrrole. Issue 41 (9th May 2017) - Ellis, Ross J.; Reinhart, Benjamin; Williams, Neil J.; Moyer, Bruce A.; Bryantsev, Vyacheslav S.
Abstract : EXAFS measurements and simulations reveal surprising interactions between the toluene solvent and the open face of the bound Cs(i ) cation that allow toluene to "cap-the-calix". Abstract : The role of solvent in molecular recognition systems is under-researched and often ignored, especially when the solvent is considered "non-interacting". This study concerns the role of toluene solvent in cesium(i ) recognition by calix[4]pyrrole. We show that π-donor interactions bind toluene molecules onto the open face of the cation-receptor complex, thus "capping the calix." By characterizing this unusual aromatically-saturated complex, we show how "non-interacting" aromatic solvents can directly coordinate receptor-bound cations and thus influence recognition.